2006
DOI: 10.1542/peds.2004-1422
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiologic Assessment of Neonatal Sleep Organization: Preliminary Results of a Randomized, Controlled Trial of Skin Contact With Preterm Infants

Abstract: The patterns demonstrated by the SSC group are analogous to more-mature sleep organization. SSC may be used as an intervention to improve sleep organization in this population of preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(115 citation statements)
references
References 72 publications
2
99
0
5
Order By: Relevance
“…Resultados semelhantes foram encontrados por Lundington-Hoe et al 14 , em um estudo randomizado envolvendo 28 RNPT com idade gestacional inferior a 32 semanas, onde foi observado, por meio de eletroencefalograma, que o grupo submetido ao MMC por até 3 h apresentou menor agitação durante todo o período do estudo, quando comparado ao grupo que recebeu os cuidados na incubadora. Do mesmo modo, no estudo de Bauer et al 15 , onde foram avaliados 27 RNPT, entre 25-30 semanas, respirando espontaneamente, observou-se maior duração de sono durante o MMC, quando comparado ao grupo controle: 90% do tempo para os de idade gestacional entre 25-27 semanas e 97% para os de idade gestacional entre 28-30 semanas.…”
Section: Discussionunclassified
“…Resultados semelhantes foram encontrados por Lundington-Hoe et al 14 , em um estudo randomizado envolvendo 28 RNPT com idade gestacional inferior a 32 semanas, onde foi observado, por meio de eletroencefalograma, que o grupo submetido ao MMC por até 3 h apresentou menor agitação durante todo o período do estudo, quando comparado ao grupo que recebeu os cuidados na incubadora. Do mesmo modo, no estudo de Bauer et al 15 , onde foram avaliados 27 RNPT, entre 25-30 semanas, respirando espontaneamente, observou-se maior duração de sono durante o MMC, quando comparado ao grupo controle: 90% do tempo para os de idade gestacional entre 25-27 semanas e 97% para os de idade gestacional entre 28-30 semanas.…”
Section: Discussionunclassified
“…Observou-se também a redução do risco de insatisfação da mãe, de falha da amamentação exclusiva na alta e a melhora do ganho ponderal durante a internação [10][11][12][13][14][15][16][17][18][19] .…”
Section: Introductionunclassified
“…214,[217][218][219] It may improve physiologic stability, 216,[220][221][222] with lower infant activity level and diminished signs of discomfort, pain or stress, although salivary cortisol as a marker of stress suggested variable infant stress response. [222][223][224] Infants demonstrate more mature sleep patterns with decreased periods of arousal and longer periods of QS and less AS, 214,217,218,222,225 and significantly decreased periods of arousal during QS There have been conflicting reports of improved weight gain and decreased length of stay 226 as well as no demonstrable difference. 220,222,227 Maternal benefits include improved parental infant attachment, improved maternal mood including feelings of self-confidence and less stress, 219,220,223,228 increased knowledge and comfort with their infant, increased maternal milk production and breast feeding.…”
Section: Role Of Sleep In Brain Developmentmentioning
confidence: 99%
“…With ambient light levels <240 lux, there was a significant increase in QS. 225 Looking at the potential impact of reduced light exposure, Roy et al 389 randomized infants to standard management or early ocular occlusion. They found that early ocular occlusion does not impair future central visual development.…”
Section: To 32 Weeks Gestational Age and Beyondmentioning
confidence: 99%